👤
a fost răspuns

3(x la a doua -4x -3 )-2 (x la adoua -5x -4)-(3x la a doua +4x-3)=

Răspuns :

3(x^2 - 4x - 3) - 2(x^2 - 5x - 4) - (3x^2 + 4x - 3) =
= 3x^2 - 12x - 9 - 2x^2 + 10x + 8 - 3x^2 - 4x + 9
= -2x^2 - 6x + 8

Presupun ca ai invatat ecuatiile de gradul 2, asa ca o sa iti las o rezolvare cu ajutorul ei.

a = -2 , b=-6  c=8
Calculam Δ = b^2 - 4ac = 36 + 64 = 100
=> x1 = (-b - √Δ)/2a = 1
=> x2 = (-b + √Δ)/2a = -4

=> -2x^2 - 6x + 8 = -2(x-1)(x+4) = (-2x+2)(x+4)

sau

-2x^2 - 6x + 8 = -2x^2 - 2x - 4x + 8 = -2x(x+1) - 4(x+1) = (x+1)(-2x-4)